Tamaño post-eclosión de los neonatos de Trachemys scripta (Testudines: Emydidae) - Cabrera Peña, Jorge (1996)
Size in hatchlings of Trachemys scripta wilh yolk sac in lhe final stage of absorption from eggs incubaled in laboratory and natural condition was determined. Statistical analysis delennined that there were not biometrical differences significative between hatchlings bom in laboratory and unde natural conditions.